The art of integrative counseling - Corey, Gerald (Belmont, CA : Brooks-Cole/Wadsworth, 2001)
This text on the art of integrative counselling helps readers learn to synthesize different theoretical approaches into a workable, individualized approach in order to work more effectively with clients.
Includes bibliographical references.
Keywords: Counseling; Psychotherapy